Analisis Kinerja Karyawan terhadap Produktivitas Kerja pada Karyawan PT.XYZ - Annora Fitriasari; Akmal Suryadi (Jurnal Ekonomi dan Bisnis Digital, 2023)
This research aims to find out how performance influences work productivity among PT. XYZ employees of East Java Province; To find out efforts to increase productivity and factors inhibiting and supporting employee performance. The research method used by the author is a qualitative method, from a research population of 23 employees, 23 employees were taken as random respondents. This research uses 5 parameters each consisting of performance variables, namely achievement, loyalty, teamwork, responsibility and quality of work. Productivity variables consist of work concentration, attendance, leadership style, entrepreneurship, and skill level. After the data collection and processing process, the results and conclusions obtained from PT. XYZ employee respondents showed that 2 of the 5employee performance variable parameters had positive values, namely teamwork and loyalty, while the other parameters showed negative values, namely responsibility, achievement and quality of work. In the productivity aspect, work concentration, leadership style and skill level received positive values, while other variables such as attendance and entrepreneurship showed negative values. Companies are advised to improve negative aspects so that the quality of employees is expected to be as planned.